2001
DOI: 10.2337/diacare.24.7.1270
|View full text |Cite
|
Sign up to set email alerts
|

Plantar Tissue Thickness Is Related to Peak Plantar Pressure in the High-Risk Diabetic Foot

Abstract: OBJECTIVE -To investigate the relationship among plantar foot pressure, plantar subcutaneous tissue thickness, severity of neuropathy (vibration perception threshold [VPT]), callus, and BMI in a large group of neuropathic diabetic patients at risk of foot ulceration. RESEARCH DESIGN AND METHODS-A total of 157 diabetic neuropathic patients (VPT Ͼ25 V) without either peripheral vascular or ulcer history were studied. Plantar foot pressure and plantar tissue thickness were measured at each metatarsal head (MTH) u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
108
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 167 publications
(119 citation statements)
references
References 29 publications
10
108
0
1
Order By: Relevance
“…As noted above, previous studies have confirmed that reduction of subcutaneous tissue under the metatarsal heads of neuropathic patients is associated with increased dynamic foot pressures and consequent increased risk of foot ulcer [61,62]. Previous anecdotal reports had suggested that the injection of liquid silicone under high-pressure areas of neuropathic feet, thereby increasing the protective "padding", was associated with reduced ulcer formation [66].…”
Section: Foot Pressure Studies In Diabetesmentioning
confidence: 79%
See 1 more Smart Citation
“…As noted above, previous studies have confirmed that reduction of subcutaneous tissue under the metatarsal heads of neuropathic patients is associated with increased dynamic foot pressures and consequent increased risk of foot ulcer [61,62]. Previous anecdotal reports had suggested that the injection of liquid silicone under high-pressure areas of neuropathic feet, thereby increasing the protective "padding", was associated with reduced ulcer formation [66].…”
Section: Foot Pressure Studies In Diabetesmentioning
confidence: 79%
“…The Planscan platform [60] allows dynamic ultrasound measurement of plantar tissue thickness while the patient is bearing weight. In a comparative study using this technique and plantar pressures measured using the pedobarograph [61], Abouaesha et al demonstrated that plantar tissue thickness under the metatarsal heads is inversely correlated with dynamic foot pressures. A follow-up study confirmed that high plantar pressure can be predicted from plantar tissue thickness with high sensitivity and specificity [62].…”
Section: Foot Pressure Studies In Diabetesmentioning
confidence: 99%
“…The ICCs for these variables were high (Ͼ0.98), which demonstrates that these variables can be assessed in a reproducible way. Small limits of agreement are important for regression analyses or correlation coefficients computed between variables of foot structure and/or foot function (3,5,6,15,16) because the outcomes from these analyses are determined by the scatter of individual cases.…”
Section: Discussionmentioning
confidence: 99%
“…Measures of structural changes and deformity in the diabetic foot have been obtained using different in vivo imaging techniques, such as ultrasound (3,17), radiography (18), and computed tomography (CT) (6,16,19,20). Saltzman et al (21) determined the interobserver variability of radiographic foot measurements in nondiabetic subjects and found a 95% limit for the MTP joint angle of 6°, which is higher than the limit in the present study (Ͻ3.0°).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation